Drivers and Risk Factors of Unplanned 30‐Day Readmission Following Spinal Cord Stimulator Implantation. Issue 1 (29th September 2017) - Elsamadicy, Aladine A.; Sergesketter, Amanda; Ren, Xinru; Mohammed Qasim Hussaini, Syed; Laarakker, Avra; Rahimpour, Shervin; Ejikeme, Tiffany; Yang, Siyun; Pagadala, Promila; Parente, Beth; Xie, Jichun; Lad, Shivanand P.
Abstract : Objectives: Unplanned 30‐day readmission rates contribute significantly to growing national healthcare expenditures. Drivers of unplanned 30‐day readmission after spinal cord stimulator (SCS) implantation are relatively unknown. The aim of this study was to determine drivers of 30‐day unplanned readmission following SCS implantation. Methods: The National Readmission Database was queried to identify all patients who underwent SCS implantation for the 2013 calendar year. Patients were grouped by readmission status, "No Readmission" and "Unplanned 30‐day Readmission." Patient demographics and comorbidities were collected for each patient. The primary outcome of interest was the rate of unplanned 30‐day readmissions and associated driving factors. A multivariate analysis was used to determine independent predictors of unplanned 30‐day readmission after SCS implantation. Results: We identified 1521 patients who underwent SCS implantation, with 113 (7.4%) experiencing an unplanned readmission within 30 days. Baseline patient demographics, comorbidities, and hospital characteristics were similar between both cohorts. The three main drivers for 30‐day readmission after SCS implantation include: 1) infection (not related to SCS device), 2) infection due to device (limited to only hardware infection), and 3) mechanical complication of SCS device. Furthermore, obesity was found to be an independent predictor of 30‐day readmission (OR: 1.86, p = 0.008). Conclusion: Our study suggests that infectious and mechanical complications are the primary drivers of unplanned 30‐day readmission after SCS implantation, with obesity as an independent predictor of unplanned readmission. Given the technological advancements in SCS, repeated studies are necessary to identify factors associated with unplanned 30‐day readmission rates after SCS implantation to improve patient outcomes and reduce associated costs.